Valuation of the Direct Benefits of Candlenut for Communities around the Forest on the Slopes of the Gawalise Mountains - Sitti Aminah; Rafiuddin; Andi Sahri Alam (Jurnal Penelitian Pendidikan IPA, 2025)
Candlenut plants can function as conservation plants to reclaim marginal lands that have been degraded. The development of candlenut plants on degraded land can not only increase the economic value of the land, but can also be used as plants with high economic value. The general objective of this study was to determine the economic value of candlenuts located on the slopes of the Gawalise Mountains in Uwemanje Village, Kinovaro Regency, Sigi Regency, Central Sulawesi. Specifically, the objectives of this study are; To determine the production of candlenut fruit, and the productivity of candlenut stands. This study uses primary data and secondary data. Primary data is obtained from direct interviews with respondents and the results of candlenut stand measurements. Secondary data is information obtained from data that is already available. both from literature and from related agencies. Data analysis uses quantitative descriptive, namely income analysis and stand productivity analysis. The results of the study showed that the community in Uwemanje Village, Kinovaro District, Sigi Regency, has obtained economic benefits from candlenut trees in the form of candlenut seed products, candlenut shells, and tree trunks. The total economic value of direct benefits of candlenut trees in Uwemanje Village, Kinovaro District, Sigi Regency, Central Sulawesi is IDR 282,950,000/year. The highest value of the three products is the average candlenut stem value of IDR 262,500,000/hectare (91.16%), then the average candlenut seed value of IDR 25,000,000/year (8.68%) and the lowest is the average shell value of IDR 450,000/year (0.16%). Of the three products, the benefits of candlenut trees that can be felt most directly and have the highest selling value are candlenut seed products because they immediately get a lot of cash from the sales.